1.2k views
5 votes
For what value of k are the roots of the quadratic equation kx (x-2)+6=0 equal?​

User Enwired
by
6.1k points

1 Answer

5 votes

Answer:


\boxed{\sf k=6}

Explanation:


\sf kx (x-2)+6=0

Expand brackets.


\sf kx^2 -2kx+6=0

This is in quadratic form.


\sf ax^2 +bx+c=0

Since this is for equal roots:


\sf b^2 -4ac=0


\sf a=k\\b=-2k\\c=6


\sf (-2k)^2 -4(k)(6)=0


\sf 4k^2-24k=0


\sf 4k(k-6)=0


\sf 4k=0\\k=0


\sf k-6=0\\k=6

Plug k as 0 to check.


\sf \sf 0x^2 -2(0)x+6=0\\6=0

False.

So that means k must equal 6.

User Lrn
by
5.8k points